2021
DOI: 10.1002/ajmg.a.62504
|View full text |Cite
|
Sign up to set email alerts
|

CTNNB1‐related neurodevelopmental disorder in a Chinese population: A case series

Abstract: CTNNB1‐related disorder is an autosomal dominant neurodevelopmental disorder characterized by a variable degree of cognitive impairment, microcephaly, truncal hypotonia, peripheral spasticity, visual defects, and dysmorphic features. In this case series, we report the clinical and molecular findings of nine Chinese patients affected by CTNNB1‐related disorders. The facial features of these affected individuals appear to resemble what had been previously described, with thin upper lip (77.8%) and hypoplastic al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 18 publications
1
32
0
3
Order By: Relevance
“…As already linked with NEDSDV (MIM# 615075) and exudative vitreoretinopathy 7 (MIM# 617572), clinical features such as developmental delay, intellectual disability, spastic diplegia, and ocular problems have been well established in CTNNB1-related neurodevelopmental disorder (1,(3)(4)(5)(6)(7)(8). Although most of our patients shared such key phenotypes, the severity of each symptom was different patient by patient.…”
Section: Discussionmentioning
confidence: 50%
See 4 more Smart Citations
“…As already linked with NEDSDV (MIM# 615075) and exudative vitreoretinopathy 7 (MIM# 617572), clinical features such as developmental delay, intellectual disability, spastic diplegia, and ocular problems have been well established in CTNNB1-related neurodevelopmental disorder (1,(3)(4)(5)(6)(7)(8). Although most of our patients shared such key phenotypes, the severity of each symptom was different patient by patient.…”
Section: Discussionmentioning
confidence: 50%
“…Although we searched for associations between mutation type or location and disease phenotype, we could not find any significant genotype-phenotype correlations in our cohort. A recent study also reported that no genotypephenotype correlations have been identified in CTNNB1-related neurodevelopmental disorder to date (15,29).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations